Others Spaces in Van - Arslan, Adile; Hurol Al, Yonca (UCEAT Chamber of Architects, 1998)
The aim of this article is to present the living conditions and spaces of the migrants, who were the victims of the technological disaster in the city of Van, Turkey.
Before deciding to build shelters for the victims of the compulsory migration, some visits were organized to Van in order to understand the living conditions of these people and the characteristics of the spaces that they use. This article was written during that initial phase of the Van Project.
Keywords: compulsory migration, shelter, technological disaster